2019
DOI: 10.1002/chem.201901086
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Sensitiveness Determination of Cubanes: Towards Cubane‐Based Fuels for Infrared Countermeasures

Abstract: As infrared seeking technology evolves, threats are better able to distinguish defensive infrared (IR) flares from true targets. Spectrally matched flares, which generally employc arbon-based fuels, are bettera ble to decoy some advanced missiles by more closely mimickingt he IR emission of the target. Cubanei sahigh-energyc arbon-based scaffold whichm ay be suitablef or use as af uel in spectrally matched flares.T he enthalpy of formation and strain energy of as eries of cubanes was predicted in silico, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…In 2012, however, Stepan and colleagues showed that a replacement of the central phenyl ring in a γ-secretase inhibitor with the bicyclo[1.1.1]pentane improved its physicochemical properties and retained bioactivity 8 11 . Later, analogous replacements were undertaken with cubane 12 19 , and bicyclo[2.2.2]octane (Fig. 1a, b ) 20 – 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, however, Stepan and colleagues showed that a replacement of the central phenyl ring in a γ-secretase inhibitor with the bicyclo[1.1.1]pentane improved its physicochemical properties and retained bioactivity 8 11 . Later, analogous replacements were undertaken with cubane 12 19 , and bicyclo[2.2.2]octane (Fig. 1a, b ) 20 – 22 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, a kilogram-scale preparation of a derivative of cubane 3 was developed, and many chemists are attempting to utilize cubane as a functional motif for applications in various scientific fields. 4,5 Recently, the application of cubane in the field of medicinal chemistry was investigated. 6 Cubane is known as a bioisostere of the benzene ring as its body diagonal length is similar to that of benzene (Scheme 1b).…”
mentioning
confidence: 99%
“…Certain functional groups are well known to substantially activate cubane derivatives. For example, 1,4-cubane-dicarboxylic acid (1 c, Figure 2) and 4-carbamoylcubane-1-carboxylic acid (4), [13] were recently disclosed by the authors to be thermally and impact sensitive. 1,4-Diisocyanocubane (5) [14] and azidocubanes (e.g., 6) [15] are observed to be highly thermally unstable and exceedingly shock sensitive.…”
mentioning
confidence: 99%
“…Certain functional groups are well known to substantially activate cubane derivatives. For example, 1,4-cubane-dicarboxylic acid (1c,F igure 2) and 4-carbamoylcubane-1-carboxylic acid (4), [13] were recently disclosedb yt he authors to be thermally and impact sensitive.1 ,4-Diisocyanocubane (5) [14] and azidocubanes( e.g., 6) [15] are observedt ob ehighly thermally unstable and exceedingly shock sensitive. 4-[(Nitrooxy)methyl]cubane-1carboxylic acid (7), dimethyl cubane-1,4-dicarboxylate (1a), and cubane-1,4-dicarboxylic acid (1c)h ave also been reported to exhibit sensitiveness to impact, [16] whereas octanitro-(8)a nd heptanitrocubane (9)a re described as insensitive to hammer taps.…”
mentioning
confidence: 99%
See 1 more Smart Citation